Analisis Faktor Penentu Potensi LP2B Menggunakan Analytical Hierarchy Process (AHP) Berdasarkan Persepsi Stakeholder (Studi Kasus : Kota Samarinda) - Purwanto, Muhammad Qoirul; Dewanti, Ajeng Nugrahaning; Pratomo, Rahmat Aris; Syafitri, Elin Diyah (COMPACT: Spatial Development Journal, 2023)
The Sustainable Food Agriculture Land (LP2B) was established by the government to maintain the sustainability of agricultural land amidst the rapid development of the global industry, which often results in a significant decline in the agricultural sector. Although the agricultural sector is a provider of the basic needs of clothing and food for a country, the registered paddy fields as LP2B have the potential to continue supplying food materials. Research by Putri (2015) indicates that changes in land use are caused by the demand for land for industry, housing, and road networks, which is also supported by the results of the study by Jean, Djuharyanto, and Nurdiani (2021) who concluded that population growth, the number of industries, the area of housing land, and the number of hotels have a significant impact on changes in the function of paddy fields in Bogor Regency. The city of Samarinda, as the study location, has issued Regional Regulation Number 06 of 2021 concerning the Protection of Sustainable Food Agricultural Land (PLP2B), which designates 1,230 hectares or about 1.7% of the total city area as LP2B with the aim of maintaining ecosystem balance and preventing the conversion of agricultural land. However, this regulation lacks consideration of important stakeholder perceptions in accommodating regional characteristics, which can provide insights and help formulate more effective and sustainable strategies (Prakoso and Munandar, 2020). This research uses the Analytical Hierarchy Process (AHP) method with 11 variables and finds that the irrigation system variable has the highest weight, while the planting index variable has the lowest weight.